Editorial - Clear, Nic; Park, Hyun Jun (Architecture Image Studies, 2021)
The proposed issue of AIS will address how some architects are embracing forms of SF to represent the intersections of these technological developments and forms of otherness and most importantly articulate those ideas through the creation of progressive architectural design position and the representation of architectural ideas. One of the objectives for a progressive speculative architecture would be to provide the visual and spatial forms that animate these narratives, giving them an immediacy and tangible presence that text alone is unable to communicate. We are living in age of great social and technological transformation: our spaces, societies, interactions and even our bodies are being transformed and the spatial consequences of our networked societies need to be fully explored as integral part of newly framed utopian architecture of the future.